A progresszió keresztény-nemzeti kísérlete a hazai nemzetiségpolitikában (1919–1920) - Orosz, László (Közép-Európai Közlemények, 2023)
The initial (albeit short) phase of the counterrevolutionary system, which came to power with the collapse of the Hungarian Soviet Republic, focused completely on preserving the territorial integrity of the state, which was its utmost political priority. This aspiration was particularly apparent in how the government expressed its accommodating posture towards the ethnic minorities residing on the territory of Hungary. By autumn 1919, the showy codification of the national minorities policy of the revolutionary period, in anticipation of the disclosure of the conditions of the peace treaty, could not be reversed since backing out of concessions made not long beforehand would clearly not have exerted drawing power on the national minorities who could still be persuaded. The counterrevolutionary ideologues were forced to acknowledge that insofar as the dominant Great Powers wished to influence by means of a more positive image of Hungary, then they too would have to feign progressivism. Progressivism associated with the leftwing and liberalism was of course out of the question! Instead a Christian, conservative, “modernly consistent” and cataclysmic ideologyfree façade that abetted peaceful symbiosis with the various ethnic minorities seemed the best course. The study examines the endeavors of the Ministry of National Minorities and the more significant measures taken to maintain territorial integrity.